ASEAN Resistance to Sovereignty Violation Interests, Balancing and the Role of the Vanguard State - Southgate, Laura (Bristol University Press, 2019)
Examining how the Association of Southeast Asian Nations' (ASEAN) has responded to external threats over the past 50 years, this book provides a compelling account of regional state actions and foreign policy in the face of potential sovereignty violation. The author draws on a large amount of previously unanalysed material, including declassified government documents and WikiLeaks cables, to examine four key cases since 1975. Taking into account state interests and the role of external powers, the author develops the 'vanguard state theory' to explain ASEAN state responses to sovereignty violation, which, it is argued, has universal applicability and explanatory power.